The use of statistical methods in creation of the urgency ranking of the land consolidation and land exchange works - Leń, Przemysław (International Conference “Environmental Engineering”, 2017)
In the analyzes of the urgency of the land consolidation and land exchange works, and particularly in the spatial comparative analyzes it is helpful to use methods of multivariate statistics, which allows the determination of synthetic measure. Synthetic measures substitute the large set of attributes of the object with one aggregate variable, allowing ordering the analyzed objects (villages) in terms of the phenomenon in question of the urgency of carrying out the work of consolidation and exchange of land. The aim of the paper is to determine measures for the urgency of carrying out the works of consolidation and exchange of land according to the method proposed by Z. Hellwig and comparison of the obtained results with the results obtained using the zero unitarisation method (ZUM). The aim of the analyzes is to verify (check), how the use of different methods of aggregation of the same diagnostic variables affects the results of research. The subject of the research consists of 14 precincts located in the municipality Białaczów, in the Łódzkie voivodship region. To construct the synthetic measure for the urgency of carrying out the works of consolidation and exchange of land 5 groups of features characterizing the works related to consolidation and exchange of land were adopted.